Response to Signature Pedagogies: A Framework for Pedagogical Foundations in Counselor Education: Through a Multicultural and Social Justice Competencies Lens - Catherine Y Chang; Ashlei Rabess (Teaching and Supervision in Counseling, 2020)
In response to Baltrinic and Wachter Morris’ challenge, the authors discuss whether the counseling profession has a signature pedagogy in the area of multicultural and social justice competencies. The authors examine broad and specific features of signature pedagogies at the professional, program, and course levels for multicultural and social justice competencies.
Keywords: signature pedagogy; multicultural counseling competencies; social justice counseling